MENGUJI MODEL TIGA FAKTOR FAMA DAN FRENCH DALAM MEMPENGARUHI RETURN SAHAM STUDI PADA SAHAM LQ45 DI BURSA EFEK INDONESIA - Bambang Sudiyatno; Moch. I rsad (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This study examined empirically Three Factor Model Fama and French on stock returns LQ 45, using data over the period 2007-2009. Specifically, this study examines the behavior of stock prices in relation to company sizeand book-to-market ratio. The main objective of this study was to provide evidence that will contribute to the effort to explain the Three Factor Model Fama and French in emerging markets.Our findings indicate asignificant positive effect between the risk premium with stock returns, while the firm size and book-to-market ratio is negatively effect, but no significant on stock returns. Therefore, the two-factor Fama and French noproven effect on stock returns.Key words: stock return, firm size, risk premium, and the book-to-market ratio.